1989
DOI: 10.1093/ajcn/50.4.773
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of protein and fat ingestion on blood glucose responses to high- and low-glycemic-index carbohydrates in noninsulin-dependent diabetic subjects

Abstract: Six noninsulin-dependent diabetic subjects received meals containing 25 g carbohydrate either as potato or as spaghetti. The meals were repeated with the addition of 25 g protein and with 25 g protein and 25 g fat. Blood glucose and insulin responses were measured for 4 h after the test meal. When carbohydrate was given alone, the blood glucose and serum insulin increments were higher for the potato meal. The addition of protein increased the insulin responses to both carbohydrates and slightly reduced the gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 23 publications
4
39
0
1
Order By: Relevance
“…The lowering of the GI of the rutab and tamer dates when eaten, albeit in a slightly lower amount, in mixed meals with yoghurt is consistent with other evidence that the presence of fat and protein in test meals affects postprandial glucose and insulin responses (Gulliford et al, 1989). However our results failed to reach statistical significance.…”
Section: Discussionsupporting
confidence: 84%
“…The lowering of the GI of the rutab and tamer dates when eaten, albeit in a slightly lower amount, in mixed meals with yoghurt is consistent with other evidence that the presence of fat and protein in test meals affects postprandial glucose and insulin responses (Gulliford et al, 1989). However our results failed to reach statistical significance.…”
Section: Discussionsupporting
confidence: 84%
“…Combined with a lowfat (30%) content, replacement of some dietary carbohydrate with protein was shown to enhance weight loss in 65 healthy overweight and obese subjects during a controlled ad libitum diet (4) as well as in 13 obese hyperinsulinemic-normoglycemic male subjects during a hypocaloric diet (5). Although an increase in the ratio of protein to carbohydrate has been shown to lower blood glucose and plasma insulin concentrations in diabetic patients (6,7), to our knowledge, the effects of fixed-intake, energy-restricted diets, with an increased ratio of protein to carbohydrate, on weight loss and energy expenditure in type 2 diabetes have not been reported.…”
mentioning
confidence: 91%
“…, 1987;Giacco et al, 2000;Gilbertson et al, 2003), a low-GI diet resulted in significant decreases in postprandial plasma glucose levels, improved glycemic control and reduction in hypoglycemic events. Results were consistent among type II diabetic patients (Jenkins et al, 1988(Jenkins et al, , 2002Gulliford et al, 1989;Wolever et al, 1992;Jarvi et al, 1999;Tsihlias et al, 2000;Heilbronn et al, 2002;Kabir et al, 2002;Brynes et al, 2003;Gilbertson et al, 2003), where low-GI diet improved plasma glucose control and had the added benefit of significantly decreasing cholesterol. Supporting the results from our study, a limited number of clinical trials have demonstrated that low-GI dietary educational interventions delivered by a clinical nutritionist can lead to improved metabolic control in patients with diabetes (Frost et al, 1994;Gilbertson et al, 2001Gilbertson et al, , 2003Rizkalla et al, 2004).…”
Section: Discussionmentioning
confidence: 58%